Inequality studies from the global South - Francis, David 1988-; Valodia, Imraan; Webster, Edward 1942-2024 (Routledge inequality studies, 2020)
"This book offers an innovative, interdisciplinary approach to thinking about inequality, and to understanding how inequality is produced and reproduced in the global South. Without the safety net of the various northern welfare states, inequality in the global South is not merely a socio-economic problem, but an existential threat to the social contract that underpins the democratic state and society itself. Only a response that is firmly grounded in the context of the global South can hope to address this problem. This collection brings together scholars from across the globe, with a particular focus on the global South, to address broad thematic areas such as the conceptual and methodological challenges of measuring inequality; the political economy of inequality in the global South; inequality in work, households and the labour market; and inequalities in land, spaces and cities. The book concludes by suggesting alternatives for addressing inequality in the global South and around the world. The pioneering ideas and theories put forward by this volume make it essential reading for students and researchers of global inequality across the fields of sociology, economics, law, politics, global studies, and development studies"--